Activities of Cellulolytic, Amylolytic, and Secondary Metabolites from Thermophilic Actinomycetes Collected from the Heated Soil around Cisolok Geyser - Sari, Dhian Chitra Ayu Fitria; Ningsih, Fitria; Rachmania, Mazytha Kinanti; Yokota, Akira; Sjamsuridzal, Wellyzar (UI Scholars Hub, 2024)
This study investigated the antimicrobial activity, cellulolytic, and amylolytic abilities of eight thermophilic Actinomy-cetes isolated from the heated soil around the Cisolok geyser, West Java, Indonesia. Cellulolytic and amylolytic abili-ties were screened for on media by adding 1% (w/v) soluble starch and carboxymethylcellulose (CMC), respectively. Antimicrobial activity was screened for using the agar-plug diffusion method by cultivating strains on various growth media. Growth at various temperatures showed that six strains could grow up to 50 °C. Seven out of eight strains showed amylolytic ability at 40 °C and 45 °C, and only four strains did so at 50 °C. Screening for cellulolytic ability showed that seven strains could hydrolyze CMC at 40 °C, whereas seven and five strains could hydrolyze at 45 °C and 50 °C, respectively. Antibacterial activity showed that strains UICC B-110 and UICC B-118 grown on various media could inhibit the growth of Gram-positive bacteria. The results of the antifungal activity test showed that strain UICC B-118, incubated for seven and 14 days, could inhibit the growth of Candida albicans. Based on 16S rRNA gene se-quence similarity and phylogenetic analyses, strains UICC B-110 and UICC B-118 were identified as Streptomyces glaucescens and Microbispora rosea subsp. rosea, respectively. These results show that thermophilic Actinomycetes from the soil around the Cisolok geyser have the potential as a source of thermostable enzymes and new bioactive compounds with antimicrobial activity.